Production of Lactuca sativa with Variations in Liquid Organic Fertilizer Concentration as an Ecoenzyme Derivative in a Hydroponic System - Mara Antero Siregar; Najla Lubis; Ruth Riah Ate Tarigan (Journal of Information Technology, computer science and Electrical Engineering, 2025)
Lettuce (Lactuca sativa L.) is a type of horticultural plant that has high nutritional content and economic value, with good prospects for development. Lettuce is an annual plant that is easy to cultivate in various types of land and has a wide market. The research was conducted to determine the response of lettuce plant production (Lactuca sativa L.) to the application of lemna leaf compost enriched with goat manure and the use of variations of liquid organic fertilizer as ecoenzymes derivative in a hydroponic system. This research used a factorial Randomized Complete Block Design (RCBD) consisting of 2 factors with 5 treatments and 3 replications. The first factor was the variation of liquid organic fertilizer from ecoenzymes at 5 levels: P0 = AB Mix (control), P1 = POC 1 (Pure EE), P2 = POC 2 (EE + egg shells + pineapple), P3 = POC 3 (EE + moringa leaves + insulin leaves), P4 = POC 4 (EE + guava leaves + sweet potato leaves + long bean leaves), P5 = POC 5 (EE + water spinach + baby corn). The second factor was the concentration of ecoenzyme at 3 levels: E0 = 0%, E1 = 25%, E2 = 50%. The observed parameters in this research included plant height (cm), number of leaves (leaves), fresh weight per plant (g), stem diameter (cm), plant weight per plot (g), and root length (cm). The results showed that POC 5 (EE + Water Spinach + Baby corn) provided fairly good results, ranking second after AB Mix, in terms of plant height (cm), fresh weight per plant (g), stem diameter (cm), plant weight per plot (g), and root length (cm). This indicates that a combination of more diverse and natural organic materials can optimally support plant growth.